Testing for Discrimination in Rental Markets: Experimental Evidence from the UK - Martin Foureaux Koppensteiner; Tania Oliveira; Nikitha Rohith (Institute of Labor Economics (IZA), 2022)
In this paper we provide novel insights on discrimination against immigrants in the UK rental market. We conducted a randomized-controlled trial close to a real-world setting where inquiries to view a property were made via phone inquiries with rental agencies and immigration background was signalled through non-UK accents. We document substantial discrimination against non-UK applicants with non-UK applicants having a 13 percent lower chance of securing a viewing for a rental. We also document substantial heterogeneous effects, with much more pronounced effects in local areas with a lower share of immigrants. We find that the background of agency managers or the composition of agency staff does not attenuate the effects.
Keywords: J15; K37; R30; 330; discrimination; rental market; immigration; right-to-rent; UK